FLORISTIC COMPOSITION AND STRUCTURE OF A PEAT SWAMP FOREST IN THE CONSERVATION AREA OF THE PT NATIONAL SAGO PRIMA, SELAT PANJANG, RIAU, INDONESIA - Rosalina, Yusi; Kartawinata, Kuswata; Nisyawati, Nisyawati; Nurdin, Erwin; Supriatna, Jatna (REINWARDTIA, 2014)
We studied the floristic composition and structure of the logged-over peat swamp forest in theÂ  PT National Sago Prima of PT Sampoerna Agro Tbk. group for future management of the conservation area that has beenÂ  set aside by the company.Â  In January - February 2012, 25 quadrats of 20 m x 20 m were laid out systematically along a transect,Â  thus covering a sampled area of 1-ha.Â  The results showed that the study site was a regenerating and developing secondary peat swamp forests having high plant species richness.Â  The total number of species recorded was 73 species of 38 families, consisting of 49 species (30 families) of trees (DBH? 10 cm ), 42 species (24 families) of saplings (H > 1.5 m and DBH < 10 cm), and 41 species (27 families) of seedlings and undergrowth.Â  Tree density was 550 individuals/ha, and total tree basal area was 18.32 m2. The Shannon-Wienerâs Diversity Index for trees was highÂ  (3.05)Â  Two tree species with the highest Importance Values (IV) were Pandanus atrocarpus (IV= 45.86 %) and Blumeodendron subrotundifolium (22.46Â  %).Â  The tree families with the highest IV were Pandanaceae (45.86), Myrtaceae (40.37), and Dipterocarpaceae (39.20). Forest structure dominated by trees with a diameter below 20 cm amounting to 408 trees/ha (74.05%). andÂ  D and E strata with height of less than 20 m, and density of 431 trees/ha (78.36%). Jaccard Similarity index among species, showedÂ  strong association between Pandanus atrocarpus and Blumeodendron subrotundifoliumÂ  and based on this association combinedÂ  with high IVs, the two parameters of speciesÂ  characterized the forest, hence the forest could be designated as the Pandanus atrocarpus--Blumeodendron subrotundifolium association. Primary forest species with high economic values were still present in the forest. Eleven species can be included in the IUCN Red List, of which Shorea rugosa is in the category of Critically Endangered), Shorea tesymanniana Endangered and Â Gonystylus bancanus vulnerable, hence they shouldÂ  be protected.